2011
DOI: 10.14411/eje.2011.013
|View full text |Cite
|
Sign up to set email alerts
|

Increasing patch area, proximity of human settlement and larval food plants positively affect the occurrence and local population size of the habitat specialist butterfly Polyommatus coridon (Lepidoptera: Lycaenidae) in fragmented calcareous grasslands

Abstract: Abstract. Which factors influence the occurrence, population size and density of species in fragmented habitat patches are key questions in population and conservation ecology. Metapopulation theory predicts that larger and less isolated habitat patches should positively influence species occurrence and population size. However, recent studies have shown that habitat quality, human activity and permeability of the landscape surrounding habitat patches may be also important. In this paper we test the relative e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…These results on population genetics are mostly supported by a classical ecological study from the Göttingen region which demonstrated that the population density of P. coridon is mainly dependent on the quantity of its larval host plant, in this case H. comosa, but not on the effect of habitat isolation and habitat quality (Krauss et al 2005). Quite similar results were obtained by Rosin et al (2011) southwest of Kraków (southern Poland); they showed that the best predictors for a potential habitat being occupied or not are its size and the percentage cover by the host plant, in this case S. varia. Hence, the chalk-hill blue is mostly dependent on the preservation of large habitats.…”
Section: Ecology Of the Imagoessupporting
confidence: 66%
“…These results on population genetics are mostly supported by a classical ecological study from the Göttingen region which demonstrated that the population density of P. coridon is mainly dependent on the quantity of its larval host plant, in this case H. comosa, but not on the effect of habitat isolation and habitat quality (Krauss et al 2005). Quite similar results were obtained by Rosin et al (2011) southwest of Kraków (southern Poland); they showed that the best predictors for a potential habitat being occupied or not are its size and the percentage cover by the host plant, in this case S. varia. Hence, the chalk-hill blue is mostly dependent on the preservation of large habitats.…”
Section: Ecology Of the Imagoessupporting
confidence: 66%
“…Human settlement also increased the number of species on verges. In farmland areas, human settlements often have small gardens with numerous flowers that can provide a supplementary resource for butterflies (Rosin et al, 2011) and this may explain the positive effects of human settlements on species richness found in our study. However, the mechanism leading to the increased proportion of roadkills is difficult to extrapolate.…”
Section: Discussionmentioning
confidence: 62%
“…The results must be viewed with reservations, however, because only four of the 54 sites surveyed were occupied by P. damon, rendering any inference rather spurious. Still, we found that both butterflies required sites with high host plant density, quite expectably in monophagous species (e.g., Krauss et al 2004;Rosin et al 2011;Roy & Thomas 2003), and both tended to occur at sites with variable management. P. thersites, but not P. damon, also increased with proportional representation of grazing, in accordance with our oviposition patterns observations.…”
Section: Discussionmentioning
confidence: 68%
“…The fate of particular species depends on a combination of species-specific habitat requirements, supply of potential habitats (area, connectivity) in a given region, and habitat quality, which can be manipulated by management of remnant habitat patches (Krauss et al 2005;Rosin et al 2011;Thomas et al 2001). Because management actions appropriate for one species may directly harm others (Bourn & Thomas 2002;Dolek & Geyer 2002), diversified land management offers the only chance to secure diverse arrays of specialised species both within insular reserves and in surrounding landscapes Morris 2000;Oliver et al 2010).…”
Section: Introductionmentioning
confidence: 99%